(untitled) (Bangladesh Journal of Physics, 2025)
Graphene oxide (GO) and its reduced form have recently attracted significant interest due to their outstanding physical and chemical characteristics, hence finding large applications in fields such as electronics and optoelectronics. The paper portrayed herein presents a simple and cost-effective route to obtaining high-quality GO through electrochemical exfoliation methods. The pre-treated Graphite powder was soaked in concentrated sulfuric acid and nitric acid in a 1:1 ratio, followed by washing and neutralization. Thereafter, it was made into paper with the aid of 1% polyethylene. The sheets were suspended in electrolyte solutions of KCl and NaCl at 10.0V, 12.5V, and 15.0V to make sure the swelling of the sheets occurred. Boiling and centrifugation are done for exfoliation and purification. Characterization of GO was performed using FT-IR, FT-Raman, and UV-vis spectroscopy. It will be verified that the voltage and electrolyte type will tune the properties and characteristics of as-prepared GO effectively. The process results in the scale-up and environmentally friendly process for GO production, making the product efficient for applications in so many high-tech industries. Bangladesh Journal of Physics, Vol. 29, Issue 2, pp. 39 – 50, December 2022